Professor de canto: atuação junto ao cantor gospel - Santos, Michael Álex dos (2021)
Introduction: Gospel singing has particularities in its form of production and possibly, also, in the way it is taught. Generally, this style of singing is expressive and performed with a lot of intensity and ornaments related to the intention of praising God. Does the singing teacher who works with the gospel singer have a different way of working? Objective: to investigate the role of the singing teacher with students of gospel singing. Method: the sample consisted of 34 singing teachers who work with gospel singing students. An online questionnaire was applied, with a focus on the characterization of the sample and open questions to investigate the existence of a working method, with its name and description, how it was constructed and the description of a class. For the answers about the name of the method, three categories were created: known methods, proper and based on theory / literature. For answers on the construction of the method, there were four categories: experience, training, observation and did not respond. Results: 34 singing teachers answered the questionnaire, 18 men and 16 women, with an average age of 37.6 years. Regarding the length of experience, 44.1% of the teachers had 11 years or more of profession and 58.8% have the teaching of singing as the only profession. Of the 34, 26 (76.47%) singing teachers responded affirmatively about having a working method. For the method name, the highlighted categories were known methods and own method, both with 46.2%. Regarding the construction of the method, the highlight was the training category with 23.1% and experience with 15.4%. Regarding the terms and / or techniques most requested by gospel singing students according to the research singing teachers, it was observed: melismas and higher notes, both with 53.8%, followed by belting with 34.6% and vibrato and vocal distortion with 26.9% each. Conclusion: in the studied group of singing teachers who have gospel singing students, most have a working method. These were divided between known and own methods, built as a result of training and experience. According to the singing teachers analyzed, melismas and high notes are the terms and / or techniques most requested by students of gospel singing